PTU-136 The outcome of lower gastrointestinal investigations in coeliac disease: a 12 year retrospective review from a district general hospital (dgh) perspective. (17th June 2017) - Patel, J; Bhuva, M; Sakthivel, GD; Rostami, K; Marsh, MN; Johnson, MW
Abstract : Introduction: Lower gastrointestinal (GI) endoscopy is frequently requested in patients with coeliac disease (CD) who present with a change in their bowel habit (CIBH), towards diarrhoea or "looser stools" (regardless of age, and often in the absence of other red-flag features such as weight-loss). This is primarily driven by the need to exclude microscopic colitis (MSC). There is, however, little evidence in the current literature to determine direct causation between CD and MSC, whilst the strength of the association is still not fully known. We set out to review the number of CD patients referred locally for lower gastrointestinal (GI) procedures, the primary referral reason and the outcomes. Method: The Luton and Dunstable University Hospital has a database of 1317 patients with coeliac disease [Male n=467, Female n=850; Age range: 1–102 years old; mean age 58]. Using the database for reference, the hospital coding system was used to analyse the total number of lower GI endoscopy procedures performed for these patients during 2005–2016. Indications for the procedures were identified, along with their further histopathological analysis. Results: Over the 12 year period, the 1317 patients underwent a total of 527 lower GI procedures; 413 colonoscopies, 108 flexible sigmoidoscopies and 6 pouchoscopies. These were performed for the following primary indications: 252 for CIBH (reflecting diarrhoea/loose stools); 53 for rectal bleeding; 52 for the Bowel Cancer Screening Programme; 54 for concomitant inflammatory bowel disease (IBD) assessment; 48 for anaemia; 21 for abnormal radiology; 15 post-cancer resection reviews; 9 for abdominal pain and 23 others. MSC was found in just 4 patients presenting with CIBH (4/252, 1.6%). Other findings included 20 new lower GI malignancies (1 with CIBH), 26 new cases of IBD (16 with CIBH), and 101 with melanosis coli (97 for CIBH, 3 for rectal bleeding and 1 for anaemia). Conclusion: 48% of the lower GI procedures performed in CD patients were due to CIBH, and MSC was only found in 4 of these patients, suggesting a weak association. Melanosis coli was histologically identified in 38.5% of procedures performed for CIBH. We know constipation is a common symptom in CD and melanosis coli is often attributed to use of laxatives, however a direct pathological link between CD and melanosis coli cannot be excluded. Consultations relating to CIBH in CD patients should focus on constipation and use of laxatives, however, the role of calprotectin +/- endoscopy remains crucial, given the number of new cases of colorectal cancer (20, 4%) and IBD (26, 5%) identified in our CD cohort. Disclosure of Interest: None Declared